Pengaruh sinar bulan terhadap telur Spodoptera exigua (Hübner) (Lepidoptera: Noctuidae) pada lahan bawang merah - Triwidodo, Hermanu; Fauziah, St Nurlaela (Jurnal Entomologi Indonesia, 2020)
Spodoptera exigua (Hübner) are nocturnal insects and one of the important pests of shallot. The activities of nocturnal insects are influenced by the moonlight. The aim of this research is to analyze the effect of moonlight on oviposition behaviour: number of egg patches, number of eggs per patches and egg gpatches distribution pattern of S. exigua. The research was done on three shallot field at Brebes Regency, Central Java during the new, half and full moon. The sampling included observing the number of egg groups, the number of eggs per egg group, and egg groups distribution pattern of S. exigua on each observation plot. The egg groups distribution pattern of S. exigua based on Morisita index. The result of this research showed that the number of egg groups and the number of eggs per egg group always increased from the new, half, and full moon. In general, the egg groups distribution pattern of S. exigua were clustered on three moonlight conditions. High intensity of moonlight (full moon) was be able to increase the number of egg groups and the number of eggs per egg groups of S. exigua, its potentially cause more attacks.